2021
DOI: 10.3390/plants10061080
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Genetic Diversity of Grapevine Viruses in Russia

Abstract: Viral diseases can seriously damage the vineyard productivity and the quality of grape and wine products. Therefore, the study of the species composition and range of grapevine viruses is important for the development and implementation of strategies and tactics to limit their spread and increase the economic benefits of viticulture. In 2014–2019, we carried out a large-scale phytosanitary monitoring of Russian commercial vineyards in the Krasnodar region, Stavropol region and Republic of Crimea. A total of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 53 publications
8
24
0
Order By: Relevance
“…At the same time, we were unable to confirm the presence of the GLRaV-2RG strain, the contigs of which were mapped to GRSLaV NC_004724.1 using two pairs of primers. Using the restrictions of the GLR2CP1/GLR2CP2 fragment, we established that MZ065369 belongs to group 3, like other Russian isolates that we found earlier in Krasnodar Krai [29]. Phylogenetic analysis of the complete nucleotide sequence of the coat protein gene of the detected isolate showed that it is 87.9% identical to the sequence of the reference genome GLRaV-2 NC_007448.…”
Section: Validation Of the Results Of Srna Hts By Rt-pcr And The Phylogenetic Analysis Of Detected Virusesmentioning
confidence: 52%
See 4 more Smart Citations
“…At the same time, we were unable to confirm the presence of the GLRaV-2RG strain, the contigs of which were mapped to GRSLaV NC_004724.1 using two pairs of primers. Using the restrictions of the GLR2CP1/GLR2CP2 fragment, we established that MZ065369 belongs to group 3, like other Russian isolates that we found earlier in Krasnodar Krai [29]. Phylogenetic analysis of the complete nucleotide sequence of the coat protein gene of the detected isolate showed that it is 87.9% identical to the sequence of the reference genome GLRaV-2 NC_007448.…”
Section: Validation Of the Results Of Srna Hts By Rt-pcr And The Phylogenetic Analysis Of Detected Virusesmentioning
confidence: 52%
“…The presence of this pathogen has been confirmed on all continents where grapes are grown [53]. In the Russian territory, this virus was previously detected in Krasnodar Krai and the Republic of Crimea [29,54].…”
Section: Validation Of the Results Of Srna Hts By Rt-pcr And The Phylogenetic Analysis Of Detected Virusesmentioning
confidence: 89%
See 3 more Smart Citations